A route to the thapsigargins from (S)-carvone providing a substrate-controlled total synthesis of trilobolide, nortrilobolide, and thapsivillosin F. - Oliver, S; Högenauer, K; Simic, O; Antonello, A; Smith, M; Ley, S (2003)
An entirely substrate-controlled total synthesis of three members of the thapsigargin family (e.g. trilobolide) is achieved starting from (S)-carvone. The synthesis is linear in nature but is achieved in high yield (> 90% per step). The route permits late-stage divergence, providing access to a range of natural products and structural analogues.